Strategi Pembentukan Karakter Kepemimpinan pada Peserta Didik melalui Ekstrakurikuler Pramuka di SMP Negeri 8 Surabaya - Kurnia Syafitri; Listyaningsih Listyaningsih (Departement of Mathematics Education, 2023)
This study aims to describe strategies for building leadership character in students through the Scout extracurricular at SMP Negeri 8 Surabaya. This study uses a descriptive qualitative research method. The theory used in this research is Thomas Lickona's character education theory. Data collection techniques in this study used in-depth interviews and observation. Informants in this study consisted of school principals, vice principals for student affairs, Scoutmasters and units, and students. The data analysis technique in this study used the Miles and Huberman model which consisted of data reduction, data display, and conclusion drawing/verification. The results obtained in this study indicate that the strategy for building leadership character in students through the Scout extracurricular at SMP Negeri 8 Surabaya is (1) Providing exemplary leadership of Scoutmasters using the among system, (2) Leadership training for students includes character building, team building, and problem solving, (3) Implementation of the team system in Scout extracurricular activities, and (4) Application of rolling leaders in Scout extracurricular activities. Through this strategy, the leadership character according to the teachings of Ki Hajar Dewantara consisting of Ing Ngarsa Sung Tuladha, Ing Madya Mangun Karsa, and Tut Wuri Handayani can be formed in students.